Marketing, livestock Development, and rangeland utilization - Swallow, B.M. (International Development Research Centre, 1992)
This chapter Reports on the major research work carried out in Lesotho and the analysis of the livestock industry in the context of rangeland utilization with overall implications for marketing. In this context the results have importance for similar livestock/range problems elsewhere in Africa. The specific production/marketing system in Lesotho is described. Results of household survey complete with partial budgets for livestock are presented. Of particular importance is the presentation of the open access and common property models in dynamic terms. They are developed in the context of the Lesotho situation.